Supercavitating vehicle maneuvering with delay and non-steady planing - Nguyen, V.; Balachandran, B. (Прикладна гідромеханіка, 2013)
In this article, a general form of pitch-plane model for supercavitating vehicle dynamics is presented and used to study vehicle maneuvers. Vehicle motions into and out of the cavity are also considered and this allows for modeling of damping-force like components encountered during planing. The non-steady nature of the planing formulation allows for appropriate treatment of transient vehicle to cavity interactions. Since the vehicle planes on a cavity that is generated by previous cavitator positions, the memory effects play an important role in the model development. Unlike previous models, which are primarily intended for studies of vehicle motions in steady horizontal travel, the current form of the model makes it possible to evaluate transient maneuvers that may deviate considerably from straight and level trajectories. A numerical optimal-control approach is utilized to generate control inputs for maneuvers intended to reach a particular location. Comparisons with previous approaches are made and results obtained for maneuvering are included in this work.